49.5k views
2 votes
Solve the quadratic equation by completing the square. 0 = x2 – 6x + 4 –4 = x2 – 6x –4 + 9 = (x2 – 6x + 9) 5 = (x – 3)2

User Sykora
by
6.1k points

1 Answer

4 votes

Answer:

x = 3±√5

Explanation:

Given the quadratic equation;

0 = x² – 6x + 4

Swap sides

x² – 6x + 4= 0

Subtract 4 from both sides

x² – 6x + 4 - 4= 0 - 4

x² – 6x = -4

Complete the square;

Add the square of half of coefficient of x to both sides

Coefficient of x = -6

Half of Coefficient of x = -6/2 = -3

square of the half of Coefficient of x = (-3)²

Add (-3)² to both sides

x² – 6x + (-3)² = -4 + (-3)²

(x-3)² = -4 + 9

(x-3)² = 5

Take the square root of both sides

x - 3 = ±√5

x = 3±√5

This gives the solution to the equation

User Sisi Mendel
by
5.2k points